Corrosion behaviour of friction-bit-joined and weld-bonded AA7075-T6/galvannealed DP980. (18th August 2017) - Lim, Yong Chae; Squires, Lile; Pan, Tsung-Yu; Miles, Michael; Keum, Jong Kahk; Song, Guang-Ling; Wang, Yanli; Feng, Zhili
ABSTRACT: Joining of aluminium alloys 7075-T6 and galvannealed dual phase 980 steel was achieved by friction bit joining (FBJ) and weld-bonding (FBJ + adhesive) processes. Accelerated laboratory-scale corrosion tests were performed on both FBJ only and weld-bonded specimens to study joint strength under a corrosive environment. Static lap shear tests showed that both FBJ only and weld-bonded cases generally retained more than 80% of the joint strength of non-corroded specimens at the end of corrosion testing. The presence of Zn/Fe coating on the steel substrate resulted in improved corrosion resistance for FBJ specimens, compared to joints produced with bare steel. An optical microscopy was used for cross-sectional analysis of corroded specimens. Some corrosion on the joining bit was observed near the bit head. However, the joining bit was still intact on the steel substrate, indicating that the primary bond was sound.